Metodologi Penafsiran Muhammad Shahrur dalam Memahami Teks (Analisis Kritis terhadap Relevansi Aplikatif Teori Limits) - R. Zainul Mushthofa (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2017)
Changing times is an unavoidable necessity along with the progress of civilization of a nation. Along with the change in the law was also progressing to adjust to the circumstances of the times. In this regard, Shahrur offers a concept in the call with the